Digital Marketing Assistance Through Instagram Social Media for Hania Home Cake's MSME Catering in Setu Subdistrict - Candra Dwi Hardiana; Kasidjo Kasidjo; Nur Azizah (Pasundan Community Service Development, 2023)
Digital marketing through social media has become a popular strategy in developing MSME businesses. Hania Home Cake, a catering business located in Setu Subdistrict, Bekasi, also utilizes social media, especially Instagram, as their primary marketing platform. However, they face several challenges such as not being listed on Google Maps, a lack of specific menu listings, poorly managed social media accounts, and suboptimal digital marketing. This study aims to provide digital marketing assistance through Instagram social media to Hania Home Cake's MSME. The research explains the concept of digital marketing, marketing strategies through Instagram, and the importance of using social media to expand reach and increase consumer awareness. In the analysis of the internal environment, weaknesses of Hania Home Cake's MSME were identified, such as underutilization of optimal technology, limited knowledge and skills in digital marketing, limited financial and workforce resources, and dependency on social media marketing. However, this study also identifies opportunities that can be utilized by Hania Home Cake's MSME, such as increasing visibility through Google Maps, creating more specific menu listings, improving the management of social media accounts, and optimizing digital marketing. It is expected that this digital marketing assistance will help Hania Home Cake's MSME enhance their online presence, expand their customer reach, and increase sales through Instagram social media.